2014
DOI: 10.1097/jom.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Habits With Accidents and Near Misses in United States Transportation Operators

Abstract: Objective To explore sleep risk factors and their association with adverse events in transportation operators. Methods Self-reported sleep-related behaviors were analyzed in transportation operators (drivers, pilots, and rail operators) aged 26 to 78 years who completed the National Sleep Foundation’s 2012 “Planes, Trains, Automobiles, and Sleep” survey. Regression analyses were used to assess the associations of various sleep-related variables with the combined outcome of self-reported accidents and near mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
4
22
1
1
Order By: Relevance
“…Still, many patients on OAT do not drive (Roncero et al, 2013). On the other hand, patients with anxiety or mood disorders, as well as patients with any type of sleep disorder, have shown an increased risk of collision (Boivin and Boudreau, 2014;Johnson et al, 2014;Karimi et al, 2014;Wickens et al, 2013). Thus, not surprisingly, patients who exhibit two risk factors for poor driving and accidents will want to drive less than patients with only one risk factor.…”
Section: Discussionmentioning
confidence: 88%
“…Still, many patients on OAT do not drive (Roncero et al, 2013). On the other hand, patients with anxiety or mood disorders, as well as patients with any type of sleep disorder, have shown an increased risk of collision (Boivin and Boudreau, 2014;Johnson et al, 2014;Karimi et al, 2014;Wickens et al, 2013). Thus, not surprisingly, patients who exhibit two risk factors for poor driving and accidents will want to drive less than patients with only one risk factor.…”
Section: Discussionmentioning
confidence: 88%
“…Shift work disorder is characterized by certain clinically significant disturbances in sleep, fatigue, and/or circadian alignment in shift workers that cannot be attributed to other causes (69). In addition, excessive daytime sleepiness due to shift work, sleep deprivation, sleep disorders, or combinations of these factors is associated with an increased risk of work-related injuries (70)(71)(72)(73). In particular, inadequately treated OSA has been found to be a contributor to many major transportation accidents (55) …”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
“…While ecological workers are not professional vehicle operators, they are operating vehicles on chemical, nuclear and remediation sites, and they are often driving early in the morning or late at night to complete their ecological studies. Sleep deprivation is a major risk factor for accidents and near misses [2]; roughly between 16 % and 20 % of all traffic accidents are related to driver sleepiness [2]. Sleeping for more than 7 hours a night is protective for accidents and near misses for transportation operators.…”
Section: Resultsmentioning
confidence: 99%
“…Further, there are regional geographic variations in work injuries that suggest that work safety measures may be unevenly distributed with respect to regional socio-economic factors [1]. Workers recognize that their jobs affect their health, and many studies are completed with self-reported conditions or health effects [2]. …”
Section: Introductionmentioning
confidence: 99%